FAMILY MORAL IDEAS AND ACTIONS AS THE DECISIVE FACTOR OF QUALITY EDUCATION IN THE CONTEXT OF SCHOOL – FAMILY – COMMUNITY PARTNERSHIP - Larisa CUZNEȚOV (Acta et Commentationes, Sciences of Education, 2019)
The article is a theoretical and applicative study related to the essence, conditions and contentof the school-family-community collaboration by analyzing the involvement of the family as an actor anddecisive factor in achieving a quality education within the social and educational partnership. It isanalyzed and established the specificity and influence of family moral ideas and actions on increasing theefficiency of collaboration within the school partnership - family - community, addressed from theperspective of the three postfigurative, cofigurative and prefigurative cultures (representing the threehuman generations).